Berberine Ameliorates Spatial Learning Memory Impairment and Modulates Cholinergic Anti-Inflammatory Pathway in Diabetic Rats - Wang, Kaifu; Chen, Qingjie; Wu, Ninghua; Li, Yong; Zhang, Ruyi; Wang, Jiawen; Gong, Di; Zou, Xin; Liu, Chao; Chen, Juan (Frontiers in Pharmacology, 2019)
Background: Cognitive impairment caused by diabetes has been recognized. Berberine is well known for its resistance to peripheral lesions, but it is rarely used for the treatment of spatial learning and memory caused by diabetes. This study explored the mechanism of berberine to alleviate cognitive impairment via the cholinergic anti-inflammatory and insulin signaling pathways. Methods: Morris water maze was used to appraise spatial learning and memory. Positron-emission tomography (PET) imaging was adopted to detect the transport of glucose, and blood/ cerebrospinal fluid (CSF) glucose was checked using commercial blood glucose meter. Insulin level was measured by ELISA kit and β-Amyloid (Aβ) formation was observed by Congo red staining. Western-blot was performed to appraise protein expression. Results: We found that berberine rectified some aberrant changes in signal molecules concerning inflammation, and cholinergic and insulin signaling pathways in the hippocampus. Furthermore, CSF/ blood glucose, inflammatory response or acetyl cholinesterase enzyme (AChE) activity were reduced by berberine. Additionally, acetylcholine levels were enhanced after berberine treatment in diabetic rats. Finally, Aβ formation in diabetic hippocampus was inhibited and spatial learning memory was ameliorated by berberine. Discussion: In conclusion, berberine clears Aβ deposit and consequently ameliorates spatial learning memory impairment via the activation of the cholinergic anti-inflammatory and insulin signaling pathways in diabetic rats.